Direct Coulomb-explosion imaging of coherent nuclear dynamics induced by few-cycle laser pulses in light and heavy hydrogen - Bocharova, I. A.; Mashiko, H.; Magrakvelidze, M.; Ray, D.; Ranitovic, P.; Cocke, C. L.; Litvinyuk, I. V. (My University, 2008)
We followed fast evolution of coherent nuclear wave packets in H2 and D2 molecules after their interaction with 8-fs 800-nm laser pulses. The molecules were probed by another few-cycle pulse time delayed for up to 10 ps with respect to the pump. For neutral molecules we observed coherent rotational dynamics characterized by periodic revivals without noticeable decoherence within the 10 ps time scale. For heavy hydrogen up to four rotational states were involved in the wave packets for each of the two spin isomers. In light hydrogen the resulting dynamics was dominated by beating of just two rotational states. For neutral molecules the experimental results are in excellent agreement with our numerical simulations obtained by solving the time-dependent Schrödinger equation. By measuring time-dependent yields for singly ionized rotating D2 molecules, we conclude that for an 8-fs 3×1014W/cm2 pulse the ionization probability is nearly independent of the angle between the molecular axis and the electric field. For those molecules that were ionized by the pump pulse we observed both vibrational and rotational dynamics. In molecular ions coherent vibrational wave packets evolving on the bound σg potential surface also exhibit revivals. Time-dependent angular distributions for the molecular ions exhibit transient alignment only soon after the pulse (18 fs for H+2 and 35 fs for D+2) with no consequent revivals within the next 10 ps due to broad distribution of active vibrational states with different rotational constants.